Cholesterol Lowering Therapies and Drugs - Huang, Chunfa; Freter, Carl (IntechOpen, 2016)
Using natural products and developing pharmaceutical drugs are emerging topics to reduce blood cholesterol levels for preventing heart disease and stroke. Covering recent progresses in cholesterol-lowering drugs and therapy, this book describes the natural and pharmaceutical products that are in clinical uses to lower cholesterol and lipids and compares these drugs in responses to different diseases such as homozygous familial hypercholesterolemia, atherosclerosis, cardiovascular disease, and cancer. The relationship between ethnicity and cholesterol-lowering drug responses is also reviewed. Each chapter is a building block for the book, but each individual chapter is also a complete subject package for the readers. Researchers from basic and clinic science interested in lipid and cholesterol metabolism, regulation, and lowering will find this book very useful. Features: - Up-to-date information of the molecular mechanisms of cholesterol lowering, the drugs from natural and pharmaceutical products, and their associated therapeutic strategies in human diseases. - Discussion of the pathogenesis of several human diseases, which are associated with high cholesterol levels and evaluation of the results of different cholesterol-lowering drug treatment in these diseases. - Discussion of the combinations of cancer chemotherapy and cholesterol lowering in potential cancer treatment and cancer prevention by cholesterol-lowering drugs. - Critical analysis of the effect of ethnicity on responses to cholesterol-lowering drug therapy leading to rational dose adjustment of cholesterol-lowering drugs for different people use.